A biomechanical, micro-computertomographic and histological analysis of the influence of diclofenac and prednisolone on fracture healing in vivo. Issue 1 (December 2016) - Bissinger, Oliver; Kreutzer, Kilian; Götz, Carolin; Hapfelmeier, Alexander; Pautke, Christoph; Vogt, Stephan; Wexel, Gabriele; Wolff, Klaus-Dietrich; Tischer, Thomas; Prodinger, Peter
Abstract Background Non-steroidal anti-inflammatory drugs (NSAIDs) have long been suspected of negatively affecting fracture healing, although numerous disputes still exist and little data are available regarding diclofenac. Glucocorticoids interfere in this process over a similar and even broader mechanism of action. As many previously conducted studies evaluated either morphological changes or biomechanical properties of treated bones, the conjunction of both structural measures is completely missing. Therefore, it was our aim to evaluate the effects of diclofenac and prednisolone on the fracture callus biomechanically, morphologically and by 3-dimensional (3D) microstructural analysis. Methods Femura of diclofenac-, prednisolone- or placebo-treated rats were pinned and a closed transverse fracture was generated. After 21 days, biomechanics, micro-CT (μCT) and histology were examined. Results The diclofenac group showed significantly impaired fracture healing compared with the control group by biomechanics and μCT (e.g. stiffness: 57.31 ± 31.11 N/mm vs. 122.44 ± 81.16 N/mm, p  = 0.030; callus volume: 47.05 ± 15.67 mm3 vs. 67.19 ± 14.90 mm3, p  = 0.037, trabecular thickness: 0.0937 mm ± 0.003 vs. 0.0983 mm ± 0.003, p  = 0.023), as confirmed by histology. Biomechanics of the prednisolone group showed obviously lower absolute values than the control group. These alterations were confirmed in conjunction with μCT and histology. Conclusions The inhibiting effects of both substances were not only mediated by absolute parameters (e.g. breaking load, BV), but we have shown, for the first time, that additional changes occurred in the microstructural bony network. Especially in patients at risk for delayed bone healing (arteriosclerosis, diabetes mellitus, smoking), the administration of these drugs should be weighed carefully.